Social Cognition in Williams Syndrome: Relations between Performance on the Social Attribution Task and Cognitive and Behavioral Characteristics - Van der Fluit, Faye; Gaffrey, Michael S.; Klein-Tasman, Bonita P. (Frontiers in Psychology, 2012)
Williams syndrome (WS) is a developmental disorder of genetic origin, with characteristic cognitive and personality profiles. Studies of WS point to an outgoing and gregarious personality style, often contrasted with autism spectrum disorders (ASDs); however, recent research has uncovered underlying social reciprocity difficulties in people with WS. Participants in the current study included 24 children with WS ages 8 through 15. A lab-based measure of social perception and social cognition was administered (Social Attribution Test), as well as an intellectual functioning measure (KBIT-II) and parent reports of communication and reciprocal social skills (Social Communication Questionnaire, Social Responsiveness Scale). Relations between social cognition, cognitive abilities, and social-communication were examined. Results demonstrated relations between parent-reported social reciprocity and the typicality of the responses provided in the lab-based measure, even once variability in intellectual functioning was taken into account. In addition, a significant improvement in performance was seen with the added scaffolding particularly for participants with stronger intellectual functioning.